2006
DOI: 10.1029/2005ja011367
|View full text |Cite
|
Sign up to set email alerts
|

Ionospheric erosion by Alfvén waves

Abstract: [1] Using observations from the FAST small explorer spacecraft, we present fields and plasma observations above the dayside auroral oval showing the erosion of ionospheric plasmas from the topside ionosphere by the action of Alfvén waves. Using interferometric techniques, the waves are shown to approximately obey the expected dispersion for Alfvén waves with transverse scales extending from greater than electron inertial lengths down to ion gyroradii. Measurements of the plasma density where these waves are ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
136
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(149 citation statements)
references
References 62 publications
13
136
0
Order By: Relevance
“…The nonlinear evolution shows the formation of electron holes structures and associated coherent (small-scale) electrostatic structures observed in auroral cavities by many spacecraft [Génot et al, 2001a[Génot et al, , 2004. More recently a comparative study conducted with FAST data [Chaston et al, 2006] revealed that predictions of the present model were actually observed (electron acceleration on the density gradients, wave focusing in the cavity, ..). On the simulation side, analog results were found independently by Tsiklauri et al [2005].…”
Section: Introductionmentioning
confidence: 90%
“…The nonlinear evolution shows the formation of electron holes structures and associated coherent (small-scale) electrostatic structures observed in auroral cavities by many spacecraft [Génot et al, 2001a[Génot et al, , 2004. More recently a comparative study conducted with FAST data [Chaston et al, 2006] revealed that predictions of the present model were actually observed (electron acceleration on the density gradients, wave focusing in the cavity, ..). On the simulation side, analog results were found independently by Tsiklauri et al [2005].…”
Section: Introductionmentioning
confidence: 90%
“…We note however that the level of electron temperature increase that is observed here cannot solely drive this instability. Chaston et al [2006] studied a similar wave spectra to that seen by the SERSIO mission which was associated with perpendicular wave heating. Their analysis of this wave activity may also prove fruitful in the investigation of ion acoustic phenomena that cause NEIAL.…”
Section: Neial and Bbelf Activitymentioning
confidence: 99%
“…Ogawa et al [2003] used DMSP and EISCAT to show that soft precipitation primarily drives ion upflow. Chaston et al [2006] used FAST data to investigate a cold ionospheric density cavity in the dayside auroral oval and found evidence of enhanced electric and magnetic field fluctuations, wave accelerated ions, and field-aligned downward directed electron fluxes. Their analysis of the downward and inward directed Poynting flux in these cavities indicated a cyclical process of Alfvén wave focusing that produces further density depletion and outflow of transversely accelerated ions.…”
Section: Introductionmentioning
confidence: 99%
“…Various mechanisms have been proposed for such acceleration, including acceleration at the edge of a potential structure [e.g., McFadden et al, 1986;Lotko, 1986] or acceleration due to broadband electrostatic turbulence [e.g., Knudsen et al, 1998]. However, the FAST spacecraft [e.g., Chaston et al, 2000Chaston et al, , 2002aChaston et al, , 2003Chaston et al, , 2006Chaston et al, , 2007 has observed these broadband distributions in conjunction with Alfvénic fluctuations, suggesting that these electrons are accelerated by parallel electric fields in kinetic Alfvén waves. This conclusion was supported by models for the Alfvén wave acceleration of these electrons [e.g., Kletzing, 1994;Thompson and Lysak, 1996;Chaston et al, 1999Chaston et al, , 2000Chaston et al, , 2002aChaston et al, , 2002bKletzing and Hu, 2001;Lysak and Song, 2003a, 2003b, which gave results consistent with observation.…”
Section: Introductionmentioning
confidence: 99%
“…Phase mixing at the plasma sheet boundary layer has been discussed by Allan and Wright [1998] and more recently by Lysak et al [2009]. Such a process could also occur at the edges of the auroral density cavity [e.g., Chaston et al, 2006;Lysak and Song, 2008].…”
Section: Introductionmentioning
confidence: 99%